Pelatihan Keterampilan Master Of Ceremony Bagi Kelompok Remaja Masjid Al-Istikmal Pademawu Sebagai Peluang Usaha di Bidang Jasa - Ria Kasanova; Muhammad Darrin Zuhri (IAI Darussalam, 2018)
The partner of this service activity is the Teenagers of Al-Istikmal Mosque, East Pademawu Village, Pademawu District, Pamekasan Regency Pamekasan. The methods for implementing the activities are as follows: (1) conduct demonstration pre-test to become MC and (2) Lecture and question and answer (3) demonstration. Community service activities with the topic of training Madurese-language master of ceremonies for the Adolescent Mosque Youth Group in East Pademawu Village went smoothly and received good responses from all participants. The 23 participants participated in full training on schedule and most of them have been able to play Madurese master of ceremonies with good intonation, attitude, and appearance as well as MCs and having and growing supporting aspects as a Madurese master of ceremony . Key Words: Master Of Ceremony, Youth Mosque, East Pademawu Village